PENDIDIKAN INDIGENOUS ALA PESANTREN UNTUK MEMPERKOKOH KARAKTER GENERASI MILENIAL - Moh. Nawafil; Hafifuddin Nur (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2020)
Pesantren’s cottage is the olddest education institute in Indonesia that the existence still be confessed in this world, education model in the style of pesantren proofed very effective to stabilizer human character, especially milenial’s generation. Milenial’s generation that shackled with technology terrible influence of information can his self and to be lessened through education in the style of pesantren who contain balance values between worldly and ukhrawi, social aspect, body aspect and spiritual, and other its as.